Producción de estructuras porosas de titania por Ice - Templating (2017)
This research had as a main point, the design and implementation of the process to produce porous structure of Titania (TiO2), with a similar density of a human bone through Ice Templating technique. The investigation was developed because of the necessity to obtain ceramic porous materials for implants and prosthesis. These ones can be obtained by the Ice templating technique, this method consists in replicate the ice structure, of Lamellar morphology, these structures move the base material and at the moment of removing the ice, the porous will stay with lamellar shape. For this investigation, the process started with a suspension of deionized water, polyvinyl alcohol, dispersant of ammonium polyacrylate and Titania (TiO2); this suspension was mixed until it became(stable and dispersed), after it was solidified (frozen), then the ice was removed by sublimation, once it was removed, the obtained structure was porous but too fragile, because of this it was...